Default and equity risk premium in the conditions of globalization and the internationalisation of the biggest capital markets of the EU and GFCI countries. Ex post implied equity premium analysis - Pera, Jacek (Niewypłacalność a premia za ryzyko kapitałowe w warunkach globalizacji i internacjonalizacji działalności największych rynków kapitałowych krajów UE i GFCI. Analiza wykonania ex post, 2019)
The purpose of the work is to examine the relationship between market risk premium and default. The research hypothesis assumes that the amount of the market risk premium significantly affects the level of the estimated probability of default of the company. The analysis was carried out using the example of the largest capital markets in the European Union and GFCI within the period from 1 January 2012 to 31 December 2018. Time series of the 20 most important stock market indices of non-financial companies representing all continents were applied in the empirical study. The largest non-financial companies, with regard to assets held as of 1 January 2012, listed on particular capital markets and included in the analyzed stock indices, one for each index, were included in the study. The following research methods were applied: the CAPM equilibrium model, Sharpe’s market asset value ratio and the market value of the corporate equity. The empirical study used time series of the 20 most important stock market indices of non-financial companies representing the analyzed markets. As a result of the analysis, the following research conclusion was established: the final value of companies from the GFCI area does not prove any significant difference with regard to their value before considering the risk premium. In the case of the EU market, this difference is significant. This means that capital markets with weaker capital and poorer, less stable economic conditions are less able to face market risk
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2019; vol. 63, nr 7, s. 82-91
Keywords: premium; market risk; liquidity; default; index; premia; ryzyko rynkowe; płynność; niewypłacalność; indeks